ChemInform Abstract: Palladium‐Catalyzed Regioselective Direct Cyanation of Acetanilide Derivatives with K4[Fe(CN)6] by C—H Bond Activation. Issue 52 (6th December 2016) - Kianmehr, Ebrahim; Faghih, Nasser; Tanbakouchian, Arezoo; Mahdavi, Mohammad
Abstract: The high‐yielding method has a good functional group tolerance.